One door closes, another opens: Surviving and thriving through organizational restructure by ensuring knowledge continuity. (December 2018) - Lambe, Andrew; Anthoney, Fiona; Shaw, Jo
Since the 2001 formation of the NHS Modernisation Agency, service improvement organizations in the NHS have regularly faced organizational restructure. Through successive restructures, there has been a growing awareness of the need to preserve organizational memory. In 2015, faced with the largest upheaval in NHS service improvement history, one knowledge team took steps to enable 'knowledge continuity' – the process of capturing organizational memory as one organization closes and transferring it to a successor organization. This article outlines the actions the team took to capture and migrate a wealth of NHS service improvement knowledge content and their actions to reconfigure the content for its new organizational home. The team selected and tagged content that aligned to business priority and enabled user access through the development of a SharePoint-based knowledge hub. With the necessary actions to secure knowledge continuity achieved, the knowledge team redefined its role, building a 5Cs knowledge service of content, curate, collaborate, consultancy and capability. The article concludes by looking positively towards the future and outlining lessons learned. With new knowledge products and an external improvement hub, and working more closely than ever before with their stakeholders, the knowledge team have not only survived organizational restructure but have begun to thrive.